Oplossing week 1

Er geldt:

$
\eqalign{
  & z^2  + z^2  = \left( {2\left( {z - 1} \right)} \right)^2   \cr
  & 2z^2  = 4\left( {z - 1} \right)^2   \cr
  & 2z^2  = 4z^2  - 8z + 4  \cr
  & z^2  - 4z + 2 = 0  \cr
  & (z - 2)^2  - 2 = 0  \cr
  & z = 2 - \sqrt 2 \,\,\left( {v.n.} \right) \vee z = 2 + \sqrt 2  \cr}
$

Of:

$
\eqalign{
  & z\sqrt 2  = z - 1 + z - 1  \cr
  & z\sqrt 2  = 2z - 2  \cr
  & 2z - z\sqrt 2  = 2  \cr
  & z(2 - \sqrt 2 ) = 2  \cr
  & z = \frac{2}
{{2 - \sqrt 2 }} = 2 + \sqrt 2  \cr}
$

©2004-2019 W.v.Ravenstein